Pengaruh Daya Tarik Konten dan Kualitas Informasi TikTok @eradotid terhadap Kebutuhan Informasi Generasi Z (Survei Pada Followers Akun TiktTok @eradotid) - Aditia Permana; Afrina Sari (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
The massive transformation of media online to social media has made social media users, especially generation Z, now able to access information or news in the process of fulfilling their information needs. This study aims to examine the influence of content attractiveness and information quality on TikTok account @eradotid towards the information needs of generation Z. The study was conducted on 100 respondents from the TikTok @eradotid followers population using multiple linear regression analysis techniques. The results show that: (1) content attractiveness has a significant influence on information needs, as evidenced by t count 3.872 > t table 1.984; (2) information quality has a significant influence on information needs, as evidenced by t count 8.621 > t table 1.984; (3) attractiveness and information quality simultaneously influence information needs, as evidenced by F count 160.740> F table 3.09 with an influence of 76.3% and 23.7% influenced by other variables not studied.